2017
DOI: 10.1002/rcs.1871
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time probe tracking using EM‐optical sensor for MRI‐guided cryoablation

Abstract: Background: A method of real-time, accurate probe tracking at the entrance of the MRI bore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results demonstrated the possibility to integrate an EM sensor into image-guided surgery with intraoperative MRI. Although replacing the EM sensor with another optical sensor may also allow the needle deflection estimation using our approach, but this EM sensor is crucial in our overall setup because we rely on the EM sensor to complete the final insertion inside the MRI bore when optical tracker fails due to line-of-sight issue [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated the possibility to integrate an EM sensor into image-guided surgery with intraoperative MRI. Although replacing the EM sensor with another optical sensor may also allow the needle deflection estimation using our approach, but this EM sensor is crucial in our overall setup because we rely on the EM sensor to complete the final insertion inside the MRI bore when optical tracker fails due to line-of-sight issue [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mala et al [6] have shown that in 28% of the cases, cryoablation of liver metastases was inadequate due to improper placement of the needles and unfavorable tumor locations. Therefore, we plan to develop a navigation system aimed at providing real-time guidance for accurate needle placement based on a two-stage scheme using both EM and optical tracker [9]. Nevertheless, as the clinicians maneuver the needle to the target location, the needle is likely to bend due to tissue inhomogeneity, tissue–needle or hand–needle interaction, fluid flow and respiration, resulting in an error in estimating the tip position [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation